PENGARUH MOTIVASI, DISIPLIN KERJA DAN KEMAMPUAN KERJA TERHADAP KINERJA PADA PEGAWAI DINAS TENAGA KERJA, TRANSMIGRASI DAN KEPENDUDUKAN PROVINSI JAWA TENGAH - Karina Ika Widyawati, 12.05.51.0017 (Students Journal of Economic and Management, 2016)
This study aims to identify and analyze the influence of motivation, work discipline and the ability to work on the performance of the employees of the Department of Manpower, Transmigration and Population of Central Java province. A sample of 100 respondents, using a quota sampling technique is a technique for determining the sample of the population that have certain characteristics to the number (quota) is desired. Samples were taken by delivering a fall or certain quorum of the group each unit consisting of a Secretariat, Sector Pentatrans, HI and Jamsos Field, Field wasnaker, Lattas Field, Field Dukcapil and Functional Division. Methods of data analysis using linear regression. The test results showed that motivation positive and significant effect on the performance of employees, work discipline and significant positive effect on employee performance and the ability to work and significant positive effect on employee performance. From the regression equation showed that the work discipline more positive effect on employee performance with a regression coefficient of 0.377; furthermore workability also a positive effect on employee performance with a regression coefficient of 0.368 and motivation positive influence on employee performance with a regression coefficient of 0.178. Keywords: motivation, work discipline, ability to work and employee performance